2017
DOI: 10.1590/1982-021620171966117
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between satisfaction aspects and the work of speech therapists of a hearing health care network

Abstract: Purpose: to correlate aspects involved in the satisfaction of speech therapists with the work in the Hearing Health Care Network regarding human resources policy, provided assistance and communication relationships. Methods: an analytical observational cross-sectional study, consisting of 27 speech therapists connected to the Hearing Health Care Network. A structured questionnaire was used as the collection instrument. A descriptive analysis of the frequency distribution of all categorical variables and analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 12 publications
(16 reference statements)
0
2
0
Order By: Relevance
“…In this study, the egresses were mostly female up to 29 years old. Studies have shown that speech therapy profession is mostly undertaken by female professionals (9,(15)(16)(17)(18)(19)(20)(21)(22) . One author relates this occurrence to the fact that women are more maternally oriented, transferring to the professional practice the tasks related to the care of another person (23) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, the egresses were mostly female up to 29 years old. Studies have shown that speech therapy profession is mostly undertaken by female professionals (9,(15)(16)(17)(18)(19)(20)(21)(22) . One author relates this occurrence to the fact that women are more maternally oriented, transferring to the professional practice the tasks related to the care of another person (23) .…”
Section: Discussionmentioning
confidence: 99%
“…A survey conducted with speech therapists found that 54.1% of professionals were dissatisfied with the profession and of these, 34.6% pointed out as a cause of dissatisfaction: low pay, 10.2%, lack of employment, 5.3%, lack of recognition and 4.0% did not justify the reason (17) . Authors discussed that compensation is one of the determining factors for professional satisfaction, as well as working conditions and staff, possibility of recognition and professional growth (17,21) .…”
Section: Discussionmentioning
confidence: 99%